The Empowerment Potentials Of Coffee Farmers By Agroindustry Practitioners Of Coffee Perfume In Kerinci Regency - Sri Wahyuni; Hery Bachrizal Tanjung; Yenny Oktavia (JERAMI : Indonesian Journal of Crop Science, 2020)
Empowerment activities to improve the ability of coffee farmers in Kerinci Regency are very important to be implemented. The purposes of this study are to describe the empowerment activities undertaken by coffee perfume agroindustry practitioners towards coffee farmers in Kerinci Regency and to explain the empowerment potentials of coffee farmers performed by coffee perfume agroindustry practitioners in Kerinci Regency. This research was designed qualitatively with descriptive methods. Data was collected using a focus group discussion (FGD) method with the informants selected in this study as many as 16 coffee farmers and Kerinci Coffee Perfume entrepreneurs themselves. Data analysis was performed using the Miles and Huberman method. The results showed that the empowerment activities carried out by coffee perfume agroindustry practitioners for coffee farmers in Kerinci Regency were still not available, because kerinci coffee perfume agroindustry practitioners only provided training to coffee farmers working in coffee farms owned by the agroindustry entrepreneurs. Meanwhile, the potential for empowerment of coffee farmers by coffee perfume agro-industry prractitioners in Kerinci Regency is very high, because the characteristics of coffee farmers that have a sense to develop and easily receive information to improve their abilities and skills in producing high quality coffee beans. Based on this, henceforth, this research can be directed at the strategy of empowering coffee farmers in Kerinci Regency by kerinci coffee perfume agro-industry practitioners and the impact of empowerment that has been done.